2014
DOI: 10.1074/jbc.m113.545194
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor GLI1 Interacts with SMAD Proteins to Modulate Transforming Growth Factor β-Induced Gene Expression in a p300/CREB-binding Protein-associated Factor (PCAF)-dependent Manner

Abstract: Background:The molecular mechanisms mediating the oncogenic activity of the transcription factor GLI1 remain elusive. Results: GLI1 interacts with SMAD factors and PCAF to regulate TGF␤-induced gene expression. Conclusion:These results define a novel epigenetic mechanism underlying the role of GLI1 as an oncogene. Significance: This study increases our understanding of gene expression regulation in cancer cells and its potential impact in tumor development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 52 publications
4
47
1
Order By: Relevance
“…As additional regulators of GLI1 activity, the SMAD2/SMAD4 and ZIC2 proteins play important roles in PDAC cells (Fig. ) . As previously mentioned, TGFβ induces SMAD3‐mediated expression of GLI2 , and consequently, the expression of GLI1 .…”
Section: Hedgehog Signaling: How It Came Onstage?mentioning
confidence: 81%
See 2 more Smart Citations
“…As additional regulators of GLI1 activity, the SMAD2/SMAD4 and ZIC2 proteins play important roles in PDAC cells (Fig. ) . As previously mentioned, TGFβ induces SMAD3‐mediated expression of GLI2 , and consequently, the expression of GLI1 .…”
Section: Hedgehog Signaling: How It Came Onstage?mentioning
confidence: 81%
“…Importantly, GLI1 has been proved to directly transactivate the expression of genes that are associated with most of these cellular functions. For instance, GLI1 directly up‐regulates the expression of CCND1 (cyclin D1), and also DNA methyltransferase DNMT1, which enhances the promoter methylation of CDKN1B (encoding p27 Kip1 ) and CDKN2C (encoding p18 INK4c ), accelerating cell‐cycle progression of PDAC cells . As for a genome instability and mutation, GLI1 directly up‐regulates BHLHE41 expression in PDAC cells .…”
Section: Hedgehog Signaling: How It Came Onstage?mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that in order to activate gene expression, Gli1 works within epigenetic complexes that decorate histone tails with various activating or repressive marks[36]. To expand on this knowledge, we performed differential expression analysis of RNA sequencing data from a variety of sources of cholangiocytes: 1) iDC; 2) the NHC cell line; and 3) isolated human cholangiocytes (IHC).…”
Section: Resultsmentioning
confidence: 99%
“…GLI1 expression construct and siRNA targeting GLI1 were described previously (35). The GLI-luciferase reporter containing eight consecutive GLI binding sites upstream of the luciferase gene (GLI-LUC) was kindly provided by Dr. Chi-chung Hui (University of Toronto, Toronto, Ontario, Canada).…”
Section: Methodsmentioning
confidence: 99%